THE RELATIONSHIP BETWEEN APPLIANCE FACTOR AND HOUSEHOLD ELECTRICITY EXPENDITURE IN THAILAND - เชยจิตร, รัชพันธุ์; สุ่มอิ่ม, ธนาธิป (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
In this study, the main objective was to find out the relationship between the appliance factor and the household electricity expenditure. Secondary data from the “2017 Household Socio-Economic Survey” complied by the National Statistical Office were employed to this study. Regarding this work, the dependent variable was the monthly household electricity expenditure and the independent variables were appliance factor, including 9 categories of the electricity appliances and the household socio-economic factors, which were gender age-groups and level of education of household head. In addition, other household characteristics were also applied to this study, including number of household member, household income, area of residences, number of room, and types of residence. Generalized Least Square (GLS) method was adopted to this study to estimate the relationship between the dependent variable and the independent variables. From obtained results showed that, when other thing being equal, there was a positive relationship between number of the electricity appliances that household occupied and the household monthly electricity expenditure, the more electricity that household occupied, the more monthly electricity expenditure. Except, household whose occupied to the laundry appliances, there was a negative relationship between number of laundry appliances and the household monthly electricity expenditure. Furthermore, the results also showed that, when other thing being equal, an increase of the air-conditioner appliance, household had a highest marginal cost of electricity, followed by the water heater, the electricity water pump, and the computer devices.